Historia, política e ideología en la celebración del Centenario mexicano - Pérez Vejo, Tomás (El Colegio de México, A.C., 2010)
In Mexico, the celebration of the independence’s hundredth anniversary was accompanied  by a complex historical-political-ideological  debate on the nature  of the nation,  the balance of a hundred years of independent life, and the problems and challenges for the future. This work analyzes, mainly through journalistic sources, this debate’s characteristics,  as well as its interpretative keys and its relevance within the process of Mexican national construction.